KALIMAT IMPERATIF BAHASA INGGRIS DAN BAHASA SIAU ( SUATU ANALISIS KONTRASTIF ) - Gaghenggang, Enrico Axel (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACTS Imperative sentence is a setence that is used to issue orders or directives.Imperative sentence contains a verb in the imperative mood. In terms of communication, imperative sentence is also used to signal, permission or any kind of exhortation. It is called illocutionary force. English and Siau language are two languages which come from different language families. English belongs to the Indo-European language, whereas Siau language belongs to Austronesian. The research questions is what the grammatical form and its meaning of imperative sentence in English and Siau language? and what are similarities and differences of English and Siau language in terms of formand meaning in communication? The objective of the research is to find out the grammatical form and its meaning in communication between English and Siau language. The data of English and Siau language is analysed based on the concept of Beaumont and Granger. The Siau data are taken from some informants who know Siau language well. It is hoped that this study can help students or readers to understand imperative sentences in terms of their differences as well as their similarities. ---------------------------------- Key word: Imperative sentence in English and Siau language, Contrastive Analysis.